Identifying Santiago's Natural Elements for Implementing an Ecological Planning Perspective. Have They Been Considered so far?. Issue 9 (February 2019) - Picon, Catalina; Barrera, Francisco de la; Fernandez, Ignacio
Abstract: Santiago, the capital and biggest city of Chile, has experienced a rapid urban growth during the last decades. This has included a large increase in population, proliferation of suburbs, and the loss and degradation of thousands of hectares of natural and semi-natural areas, whose natural elements may play a key role for the city's sustainability. Taking into consideration the relevance of these natural elements for Santiago's future planning efforts, in this work we take an ecological planning approach, -where ecological and environmental considerations are set in the front, to identify Santiago's natural elements and assess how they are, and have been incorporated, in local and regional planning regulations. To achieve this goal, we first analyzed the city's geographical components using an ecological planning framework to identify the most relevant natural elements that could be considered worth to be included in planning regulations at the local and regional scales. The framework promotes the conservation and connectivity of natural, agricultural, peri-urban, and urban landscapes at the regional and local scale. Then, we analyzed past and present planning instruments to evaluate how they have incorporated the identified natural elements, and how these regulations (or the lack of them) may have driven the regional and local landscapes at its current state. Our results show that the identified natural elements have been rarely formally recognized in planning instruments, and therefore not taken in consideration for urban planning. Consequently, most of natural elements that are identified as relevant for ecological planning in Santiago are currently degraded. Nevertheless, these natural elements still provide valuable opportunities for increasing Santiago's sustainability if restored and conserved, and if they are better incorporated in planning regulations. The few regulations recognizing the natural elements do not indicate how to protect or conserve them, nor how they should be managed to provide benefits to the city. We conclude that in Santiago is imperative to modify current planning regulations, to effectively safeguard the conservation of these key natural elements, and to promote a better interconnection among natural, agricultural, peri-urban and urban landscapes at multiple scales.